Pelatihan Pembuatan Ramuan Herbal Pada Kelompok Peternak Ayam Kampung di Desa Werwaru, Kecamatan Moa, Kabupaten Maluku Barat Daya - Juwaher Makatita (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Community service activities aim to provide training for local chicken farmers about herbal concoctions in the form of a mixture of lemongrass stalks, ginger, turmeric, galangal, garlic and brown sugar to improve the health of local chickens which will later support the growth and maintain the immunity of the local chickens. The method of implementing community service carried out to the local chicken farmer group in Werwaru Village, Southwest Maluku Regency is by using lecture methods, discussions and direct practice on making and using herbal concoctions that are given directly to local chickens. The results of the implementation of this community service are able to increase the knowledge of farmers, especially in making herbal concoctions to maintain the stamina and immunity of local chicken health. The conclusion of this community service is that training in making herbal concoctions in the form of a mixture of lemongrass stalks, galangal, ginger, brown sugar, garlic for local chickens is very interesting and of interest to farmers and increases farmers' understanding of the importance of using herbal ingredients that are around the farmer's environment to support the health of livestock, both local chickens and other livestock that are kept.